2005
DOI: 10.1002/maco.200503922
|View full text |Cite
|
Sign up to set email alerts
|

New oxidation-resistant coatings for steam power plants at 650 °C

Abstract: The increase of live steam temperature and pressure in new steam power plants is certainly the most effective measure to realize the stipulated CO 2 reduction targets for the conventional power industry. The development of new materials becomes a key challenge on the way forward to a more efficient and sustainable power generation. There are two approaches being followed in materials technology in order to facilitate higher steam temperatures and pressures in the water steam cycle: 1.) The development of new m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Other studies at elevated pressure have been performed on SiC [29,30]. In some of the mentioned work, an increase in oxide scale growth at elevated pressure was found [17,24,27,28], while other studies found similar or enhanced oxide scale growth at atmospheric pressure [23,25,26]. A possible explanation for enhanced scale growth at elevated pressure is an increase of diffusion rates in the oxide and alloy [24,28,31].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies at elevated pressure have been performed on SiC [29,30]. In some of the mentioned work, an increase in oxide scale growth at elevated pressure was found [17,24,27,28], while other studies found similar or enhanced oxide scale growth at atmospheric pressure [23,25,26]. A possible explanation for enhanced scale growth at elevated pressure is an increase of diffusion rates in the oxide and alloy [24,28,31].…”
Section: Introductionmentioning
confidence: 95%
“…Studies at elevated pressure showed changes in the high temperature corrosion behavior, as reported e.g., for dry air [16], supercritical CO 2 [17][18][19][20][21] or carburizing atmospheres [14,22]. Corrosion issues in steam turbines have initiated research on water vapor-induced oxidation at elevated pressure in static or flowing pure steam [17,[23][24][25][26][27][28]. In these studies, Fe-and Ni-base alloys were tested.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the standard procedure are given in Table 3. This paper concentrates on the results of steam oxidation testing for 1000 h; results for longer testing times have been presented elsewhere 9–13.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Therefore oxidation resistant coatings [7], which form a stable and slow growing oxide as a barrier to oxidation [8], are now being considered when applied to P92. Aluminide diusion coatings have traditionally been the focus of coated P92 research.…”
Section: Introductionmentioning
confidence: 99%